2012
DOI: 10.1021/jp301399b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Study of the Interfacial Structure and Differential Capacitance of Alkylimidazolium Bis(trifluoromethanesulfonyl)imide [Cnmim][TFSI] Ionic Liquids at Graphite Electrodes

Abstract: The dependence on electrode potential of the interfacial structure and differential capacitance (DC) for 1alkyl-3-methyimidazolium bis(trifluoromethanesulfonyl)imide ([C n mim][TFSI], n = 2, 4, 6, and 8) ionic liquids (IL) near basal (flat) and prismatic edge face (rough) graphite electrodes was investigated here with atomistic simulations. Overall camel-shaped DCs were observed for both surfaces. The prismatic graphite generated systematically larger capacitances than the atomically flat basal face. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
162
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(187 citation statements)
references
References 130 publications
20
162
5
Order By: Relevance
“…51 Theoretical studies confirmed the existence of spatial heterogeneities at the interface due to the formation of polar and non-polar domains of the IL-molecules, as well as the existence of highly compressible alternating multilayers. 52,53,54,55,56 At very high negative potentials we could not find ordered superstructures such as those exist on Au(100) in BMIPF6, where ordered double-row structures of the cations could be observed (Fig. 9.…”
Section: In-situ Stmmentioning
confidence: 74%
“…51 Theoretical studies confirmed the existence of spatial heterogeneities at the interface due to the formation of polar and non-polar domains of the IL-molecules, as well as the existence of highly compressible alternating multilayers. 52,53,54,55,56 At very high negative potentials we could not find ordered superstructures such as those exist on Au(100) in BMIPF6, where ordered double-row structures of the cations could be observed (Fig. 9.…”
Section: In-situ Stmmentioning
confidence: 74%
“…MD simulations have addressed the unique potential influence on DC curve through analysis of cumulative density of specific groups and atoms in RTILs. 35 …”
Section: Ion Size Effectmentioning
confidence: 99%
“…Merlet et al [24][25][26][27] studied a nanoporous carbon electrode in contact with electrolyte consisting of an ionic liquid or an ionic liquid/acetonitrile mixture. Vatamanu and co-workers [28][29][30][31] investigated ionic liquid electrolytes with carbon or gold electrodes using the smooth particle mesh Ewald (SMPE) 32,33 method to simplify the calculation. The hydration of metal-electrode surfaces was examined by Limmer et al 34,35 In all of these studies, detailed comparisons of the CPM with the fixed charge method have been lacking.…”
Section: Introductionmentioning
confidence: 99%